2019
DOI: 10.15578/jra.14.4.2019.213-223
|View full text |Cite
|
Sign up to set email alerts
|

PENGARUH APLIKASI dsRNA VP-15 IN VITRO DAN IN VIVO TERHADAP SINTASAN DAN RESPONS IMUN UDANG WINDU Penaeus monodon

Abstract: Teknologi RNA interference (RNAi) merupakan salah satu pendekatan yang digunakan untuk meningkatkan resistensi udang windu terhadap infeksi patogen termasuk WSSV. Pengembangan teknologi RNAi melalui aplikasi untai ganda RNA (dsRNA) yang berasal dari gen pengkode viral protein (VP) dari WSSV telah mulai dikembangkan pada udang. Penelitian ini bertujuan untuk mengkaji sintasan dan respons imun udang windu yang diberi VP-15 pasca uji tantang dengan WSSV. Udang windu (panjang 15,21 ± 1,19 cm dan bobot 32,5 ± 1,83 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…A study of the dsRNA VP-24 vaccine at a dose of 0.2 μg showed a significant increase in survival rate in tiger shrimp by 65% compared to control (10%) (Mulyaningrum et al, 2018). Some studies also demonstrated that the intramuscular injection and oral delivery of dsRNA can provide better protection than control groups of tiger shrimp (Puneeth et al, 2017) and our studies indicated that the application of dsRNA by injection showed a better survival response than oral administration (Mulyaningrum et al, 2018;Parenrengi et al, 2018;2019). The shrimp survival by injected with dsRNA of VP24, VP19 and VP15 (Sarathi et al, 2010) and VP28 (Nilsen et al, 2017;Sarathi et al, 2008;Solis-Lucero et al, 2016) was significantly higher than that of control groups.…”
Section: Survival Ratesupporting
confidence: 54%
See 2 more Smart Citations
“…A study of the dsRNA VP-24 vaccine at a dose of 0.2 μg showed a significant increase in survival rate in tiger shrimp by 65% compared to control (10%) (Mulyaningrum et al, 2018). Some studies also demonstrated that the intramuscular injection and oral delivery of dsRNA can provide better protection than control groups of tiger shrimp (Puneeth et al, 2017) and our studies indicated that the application of dsRNA by injection showed a better survival response than oral administration (Mulyaningrum et al, 2018;Parenrengi et al, 2018;2019). The shrimp survival by injected with dsRNA of VP24, VP19 and VP15 (Sarathi et al, 2010) and VP28 (Nilsen et al, 2017;Sarathi et al, 2008;Solis-Lucero et al, 2016) was significantly higher than that of control groups.…”
Section: Survival Ratesupporting
confidence: 54%
“…In contrast, Parenrengi et al (2019) reported that dsRNA vaccine had a significant effect on the proPO activity of tiger shrimp, where the highest proPO activity was obtained in the in-vivo VP15 dsRNA and subsequently invitro and the lowest in control (without dsRNA). This study also revealed that proPO activity increased the longer test animals were exposed to W SSV.…”
Section: Prophenoloxidase Activitymentioning
confidence: 89%
See 1 more Smart Citation
“…As a preliminary step, isolation and characterization of the coding genes VP-24 and VP-15 [15] and [16]has been carried out as well as their application in the form of recombinant DNA dsRNA, which has been constructed and produced in-vitro using mega script RNAi kits [17,18]. The optimal injection dose can be obtained in fighting white spot disease in tiger shrimp [19]. In-vivo production of dsRNA is carried out by cloning of the VP-WSSV gene in the RNAi vector and transformation in the competent of E. coli bacteria that can produce plasmids.…”
Section: Introductionmentioning
confidence: 99%
“…That issue made (Luo et al, 2003) conducted the first study with the transfer of the antiviral gene PmAV and the results showed that the transfer of antiviral genes could reduce the attack of WSSV pathogens on tiger shrimp. Parenrengi et al, (2019)…”
Section: Introductionmentioning
confidence: 99%